Colchicine improved pediatric acute refractory idiopathic pericarditis. Issue 2 (3rd July 2017) - Hayashi, Takahiro; Baba, Shiro; Toyoda, Naoki; Tahara, Junko; Yachie, Akihiro; Izawa, Kazushi; Yasumi, Takahiro; Nishikomori, Ryuta; Heike, Toshio
Abstract: Colchicine is an anti-inflammatory drug. The combination of colchicine and NSAIDs is the first-line therapy for acute pericarditis in adults. However, in children, colchicine is recommended only for recurrent pericarditis, and its efficacy against acute pericarditis is unknown. This study describes a 6-year-old boy who suffered from acute idiopathic pericarditis that was refractory to aspirin and ibuprofen. Colchicine led to a marked improvement in his symptoms (fever and pericardial effusion) and inflammatory data. It also prevented disease recurrence. An ascending dose regimen also prevented gastrointestinal side effects. Thus, colchicine should be useful for refractory cases of acute idiopathic pericarditis in children.